Development and Evaluation of a Continuous Cocoa Pod Breaker - SRIKANTH VANKAYALAPATI; Dr. Rajesh G.K (Guide) (Tavanur 2017 Department of Food and Agricultural Process Engineering)
Development and Evaluation of a Continuous Cocoa Pod Breaker
Development and Evaluation of a Continuous Cocoa Pod Breaker